The seven "laws" of training - Hatfield, F. C.
n discussing training, you will come across a numerous number of training "do`s and don`ts" in training. However, in one way or another it will comedown to 7 basic training principles ("Laws" really, as they have stood the test of time!) that must be present when constructing and engaging in atraining program. These seven principles (or "Laws") are: 1. The Principle of Individual Differences. 2. The Principle of Overcompensation. 3. The Principle of Overload. 4. The Specific Adaptation to Imposed Demands (SAID) Principle. 5. The General Adaptation Syndrome (GAS) Principle. 6. The Use/Disuse Principle. 7. The Specificity Principle.